STANDARDIZATION VS. ADAPTATION DILEMMA: A COMPARATIVE ANALYSIS OF KOREAN BEAUTY BRAND MARKETING STRATEGIES ACROSS GEOGRAPHIC MARKETS - Aziz Kurbanovich Abdullaev; Ozodbek Ne’matjon o‘g‘li Mirzorakhimov (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: The global expansion of Korean beauty (K-Beauty) brands presents one of the most instructive contemporary cases of international marketing strategy under conditions of extreme market heterogeneity. A single KERASYS shampoo retailing at five to six US dollars in Uzbekistan represents a cost burden on the average consumer approximately 8.7 times heavier — measured as a share of monthly income — than the identical purchase for a Korean consumer at home. Yet this product commands aspirational import status in Central Asian retail chains, functions as a mass-market commodity in Seoul drugstores, and enters the United States as a clinical-grade innovation import priced at fourteen to twenty dollars. This paper examines how two flagship Korean FMCG groups — Aekyung Group (KERASYS, Dr.Rooteer) and AmorePacific Corporation (Laneige, Innisfree) — calibrate their marketing strategies across five structurally distinct markets: Uzbekistan and Central Asia, South Korea (home market benchmark), the United States, Southeast Asia, and the Gulf Cooperation Council (GCC). Employing a mixed-methods design that combines primary consumer survey data collected in Tashkent, Uzbekistan (n=36) with systematic secondary data analysis drawn from corporate earnings disclosures, retail trade intelligence, peer-reviewed academic journals, and industry market reports, the study generates four original contributions to the international marketing literature. First, it establishes that purchasing power parity — operationalized through a novel Price Accessibility Index (PAI) — is a more powerful determinant of pricing and channel adaptation than cultural distance metrics.